55 Quality Improvement Project to Assess How Informed Patients are About do not Attempt Cardiopulmonary (DNACPR) Decisions?. (6th February 2020) - Jayasuriya, P; Amanullah, Y; Kumar, A; Hookey, C
Abstract: Introduction: Despite growing evidence regarding DNACPR decisions, there is a paucity of information given to patients regarding resuscitation decisions. The main aim of this quality improvement project was to assess and improve patients' and their relatives' understanding about DNACPR decisions. Intervention: We initially surveyed 30 inpatients or their next-of-kin (if the patient lacked capacity) in a geriatric ward who had DNACPR decisions in place. Although, 86% knew the implications of a DNACPR decision, only 50% knew that a DNACPR decision would not limit them from receiving other treatment. 66% reported that the information given by the healthcare professional is "too little". 35 questionnaires were also given to doctors of all grades to assess their practice of DNACPR discussions and barriers for discussion. Majority (95%) of doctors knew what should be included in a DNACPR discussion. Medical staff not considering DNACPR discussions during assessment, medical staff not comfortable to make the DNACPR decision and the fear of distressing the patient are the three main issues that were highlighted as barriers. 17% of doctors reported that they would have attended a cardiac arrest at least on 2-5 occasions for a patient when resuscitation was futile. We presented this data and educated doctors on effective DNACPR discussions using video demonstrations in weekly journal clubs. All doctors were informed to distribute DNACPR Improvement: After the intervention, only 80% understood the DNACPR discussion. 76% knew that DNACPR does not limit them from receiving other treatment. 73% reported that this was not stressful and 76% were satisfied with the discussion and reported that their questions were answered adequately. 11 out of 30 patients had received the information leaflets and all found it useful. Discussion: Although after the intervention the percentage who understood the DNACPR decision had reduced compared to the initial audit, there was a 20% improvement in who knew that DNACPR decisions did not limit other treatment. We hope to extend this study by carrying out training sessions for doctors to improve the quality of these conversations and thereby enhance adherence to expected practice in DNACPR decision making.